BS ISO 6650. Fertilizers, Soil conditioners and Beneficial Substances. Simultaneous Determination of N-buthylthiophosphorus Triamide (NBPT) and Dicyandiamide (DCD) by High-performance Liquid Chromatography (HPLC). (24th August 2022) - British Standards Institution,
No abstract available